How are Competing Logics Combined in Managerial Teams? The Impact of Branch Founding Team Hybridity on the Growth of Islamic Bank Branches in Turkey, 2002–19. (30th November 2021) - Boone, Christophe; Özcan, Serden; Li, Jia
Abstract: Hybrid staffing – i.e., composing a workforce with individuals with oppositional institutional logics – is a strategy organizations can use to navigate through complex institutional environments. We propose that hybrid teams led by individuals with the legitimate logic from the perspective of the target audiences (conformist‐led hybrids) will outperform all‐conformist, non‐hybrid teams, and that hybrid teams led by individuals with the contested logic (alien‐led hybrids) will underperform non‐hybrid teams. Moreover, the performance advantage of conformist‐led hybrids will be attenuated by ideological polarization and demographic stability of the embedding community, and the performance disadvantage of alien‐led hybrids will be exacerbated by these two community characteristics. We tested our multilevel contingency model with the newly founded Islamic bank branches in Turkey in 2002–19. We found that the conformist‐led hybrids had a growth advantage over non‐hybrids, and alien‐led hybrids had a growth disadvantage, especially when the embedding communities were ideologically polarized. Theoretical implications are discussed.